The 2010 IEEE International Conference on Information and Automation 2010
DOI: 10.1109/icinfa.2010.5512419
|View full text |Cite
|
Sign up to set email alerts
|

Path tracking control considering center of gravity shift and load change for an omni-directional walker

Abstract: Walking is a vital exercise that is very important for health and everyday life. In the authors' previous studies, an omni-directional walker was developed for walking rehabilitation. Walking training programs are stored in the walker so that rehabilitation can be carried out without a physical therapist. However, the walker sometimes strays from the predefined path due to a center of gravity shift and load change. It is necessary for the walker to precisely follow the paths defined in the walking training pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…So the motors provided the same force when the different weight patients trained using the walker. Adaptive control method for the omnidirectional walker is discussed in [11][12][13], the kinetics equation was improved by considering the centerof-gravity shifts and load changes caused by users. The adaptive controller had obtained favourable tracking effect.…”
Section: Introductionmentioning
confidence: 99%
“…So the motors provided the same force when the different weight patients trained using the walker. Adaptive control method for the omnidirectional walker is discussed in [11][12][13], the kinetics equation was improved by considering the centerof-gravity shifts and load changes caused by users. The adaptive controller had obtained favourable tracking effect.…”
Section: Introductionmentioning
confidence: 99%
“…To operate effectively in real‐world applications, the control algorithm must guarantee that these actuators can follow a prescribed path accurately. Note that all existing results were obtained under the assumption that the actuator motors are fault‐free for rehabilitative robots . However, in practical applications, actuator failures and saturation are often unavoidable.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that tracking neglects the mass and inertia matrix when the loads are overweight, and consequently tracking precision is reduced. An adaptive control method for the ODW was discussed in [6][7][8]. The kinetic equation was improved by considering the center of gravity shifts and load fluctuations caused by users.…”
Section: Introductionmentioning
confidence: 99%